Association between transportation barriers and anticoagulation control among an inner‐city, low‐income population: A prospective observational cohort study. Issue 7 (31st October 2021) - Yan, Connie H.; Naveed, Maryam; Alobaidi, Ali; Kopfman, Miranda; Nutescu, Edith A.; Sharp, Lisa K.
Abstract: Background: Anticoagulation with warfarin represents a transportation‐sensitive treatment state. Transportation barrier is a common reason for not using health care services. Objective: To assess the association between transportation barriers to anticoagulation clinic and anticoagulation control (AC) among an inner‐city, low‐income population. Patients/Methods: Adults expected to be on chronic warfarin therapy were recruited from an ambulatory anticoagulation clinic. Participants completed a validated questionnaire that assessed transportation barriers to clinic, defined as self‐reported trouble getting transportation to a clinic and a composite score of the presence of transportation barriers. Suboptimal AC was defined as time in therapeutic range (TTR) <60% over 6 months. Prevalence ratios with 95% confidence intervals (CIs), adjusted for age, sex, and annual household income, described the association of transportation trouble and barriers with AC. Results: Of 133 participants, 42.9% had suboptimal AC. Mean age was 60.4 (SD, 13.6) years, and the majority of participants were women (62.2%). Participants with transportation trouble were more likely to report being disabled/unable to work (63.6%) and annual household income <$15 000 (45.5%). Mean TTR was significantly lower for participants with transportation trouble compared to those without (53.8% [SD, 24.7%] vs 64.7% [SD, 25.0%]; P  = .03). Participants reporting transportation trouble or at least one transportation barrier were 1.60 (95% CI, 1.07‐2.39) and 1.68 (95% CI, 1.01‐2.80) times more likely, respectively, to have suboptimal AC compared to those without. Conclusion: Inner‐city, low‐income individuals with transportation barriers were more likely to have suboptimal AC. Further research is warranted to evaluate the impact of alleviating patient‐specific transportation barriers on anticoagulation outcomes.